Generation of live mice from haploid ESCs with germline-DMR deletions or switch - Yongjian Ma; Meng Yan; Zhenfei Xie; Hongling Zhang; Zhoujie Li; Yuanyuan Li; Suming Yang; Meiling Zhang; Wen Li; Jinsong Li (Cell Discovery)
Abstract Genomic imprinting is required for sexual reproduction and embryonic development of mammals, in which, differentially methylated regions (DMRs) regulate the parent-specific monoallelic expression of imprinted genes. Numerous studies on imprinted genes have highlighted their critical roles in development. However, what imprinting network is essential for development is still unclear. Here, we establish a stepwise system to reconstruct a development-related imprinting network, in which diploid embryonic stem cells (ESCs) are derived by fusing between parthenogenetic (PG)- and androgenetic (AG)-haploid embryonic stem cells (haESCs) with different DMR deletions (termed Ha-Ha-fusion system), followed by tetraploid complementation to produce all-haESC fetuses. Diploid ESCs fused between PG-haESCs carrying 8 maternally-derived DMR deletions and AG-haESCs with 2 paternally-derived DMR deletions give rise to live pups efficiently, among which, one lives to weaning. Strikingly, diploid ESCs derived from the fusion of PG-haESCs with 7 maternal DMR deletions and AG-haESCs with 2 paternal DMR deletions and maternal Snrpn-DMR deletion also support full-term embryonic development. Moreover, embryos reconstructed by injection of AG-haESCs with hypomethylated H19-DMR into oocytes with H19-DMR deletion develop into live mice sustaining inverted allelic gene expression. Together, our findings indicate that restoration of monoallelic expression of 10 imprinted regions is adequate for the full-term development of all-haESC pups, and it works irrespective of their parental origins. Meanwhile, Ha-Ha-fusion system provides a useful tool for deciphering imprinting regulation networks during embryonic development.